2011
DOI: 10.1002/zoo.20428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three protocols for superovulation of brown brocket deer (Mazama gouazoubira)

Abstract: This study aims to evaluate the ovulation rate and the presence of functional corpora lutea after treatment by three different protocols designed to cause superovulation in brown brocket deer. Six female received an intravaginal device containing 0.33 g of progesterone (CIDR®) for 8 days, followed by 0.5 mg injection of estradiol benzoate at the time of insertion and 265 µg of cloprostenol at the time of removal. Afterwards, the hinds were divided into three groups (n = 2): Treatment A received injection of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
3
11
1
Order By: Relevance
“…Moreover, this mean was higher than the ovulation means obtained for other species, such as E. davidianus (CL 3.83 [15]), O. virginianus (3.10 CL [19]) and C. elaphus , which were not selected for a MOET program (2.15 CL [14]). Higher mean ovulation (3.40 ± 0.68 CL) has already been obtained for the species M. gouazoubira , in a previous experiment which used similar SOV protocols with modifications in the EB dosage (0.5 mg) used to induce ovulatory follicular atresia and synchronize the follicle wave in conjunction with the CIDR® and eCG (600UI) used to induce SOV [7]. …”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Moreover, this mean was higher than the ovulation means obtained for other species, such as E. davidianus (CL 3.83 [15]), O. virginianus (3.10 CL [19]) and C. elaphus , which were not selected for a MOET program (2.15 CL [14]). Higher mean ovulation (3.40 ± 0.68 CL) has already been obtained for the species M. gouazoubira , in a previous experiment which used similar SOV protocols with modifications in the EB dosage (0.5 mg) used to induce ovulatory follicular atresia and synchronize the follicle wave in conjunction with the CIDR® and eCG (600UI) used to induce SOV [7]. …”
Section: Discussionmentioning
confidence: 94%
“…The use of a lower dose of EB and a higher dose of eCG seem to have been a positive factor. It has already been shown that high levels of estradiol at the moment of insertion of the progesterone implant and early administration of gonadotropins have a negative impact on superovulatory response and on follicular wave synchronization [23,42] and that the ovulation rate increases in a dose-dependent manner [43] in relation to an increase in the eCG dosage [7]. However, even using a lower dose of EB, it is probable the protocol is not yet well adjusted to the needs of this species, since the hinds presented behavioral estrus following the administration of EB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations